Long non-coding RNA profiling in LPS-induced intestinal inflammation model: New insight into pathogenesis. Issue 8 (November 2019) - Guo, Ling; Li, Linna; Zhang, Yang; Fu, Shulin; Zhang, Jing; Wang, Xiuying; Zhu, Huiling; Qiao, Mu; Wu, Lingying; Liu, Yulan
LPS can induce an inflammatory immune response in the intestine, and long non-coding RNA (lncRNA) is involved in the process of inflammatory disease. However, the biological role of lncRNA in the intestinal inflammation of piglets remains unclear. In this study, the lncRNA expression profile of the ileal mucosa of piglets challenged by LPS was analysed using lncRNA sequencing. In total, 112 novel lncRNAs were predicted, of which 58 were up-regulated and 54 down-regulated following LPS challenge. Expression of 15 selected lncRNAs was validated by quantitative PCR. We further investigated the target genes of lncRNA that were enriched in the signalling pathways involved in the inflammatory immune response by utilising Gene Ontology and Kyoto Encyclopaedia of Genes and Genomes analysis, with cell adhesion molecules and mTOR signalling pathway identified. In addition, the co-expression networks between the differentially expressed lncRNAs and the target mRNAs were constructed, with seven core lncRNAs identified, which also demonstrated that the relationship between lncRNAs and the target genes was highly correlated. Our study offers important information about the lncRNAs of the mucosal immune system in piglets and provides new insights into the inflammatory mechanism of LPS challenge, which might serve as a novel target to control intestinal inflammation.